2009
DOI: 10.5539/ass.v4n12p113
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Students Teaching Quality Determinants and Effectiveness

Abstract: The purpose of this study is to examine the perceptions among students from three public Universities, particularly students from Universiti Teknologi MARA, Universiti Sains Malaysia, and Universiti Utara Malaysia towards lecturers teaching Quality determinants. A field survey among students from different field of studies (Social Sciences and Pure Sciences) was conducted through a questionnaire. The data were factor-analyzed to determine the key dimensions of lecturers teaching quality. The resulting dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The study conducted by Hussin, Jusoff, Omar (2008) to evaluate students" perception towards factors determining lecturers" teaching ability, showed that seventeen dimensions, namely: clarity, practicality, exercises, attention, enthusiasm, creativity, feedback, syllabus, motivation, extra reading, availability, technology, punctuality, current issue, approachable, language use, and communication help in differentiating lecturers" teaching performance and students" perceptions of teaching quality. The findings of this study suggest that the lecturers should consider these dimensions during lecturer-student interaction in the classroom.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The study conducted by Hussin, Jusoff, Omar (2008) to evaluate students" perception towards factors determining lecturers" teaching ability, showed that seventeen dimensions, namely: clarity, practicality, exercises, attention, enthusiasm, creativity, feedback, syllabus, motivation, extra reading, availability, technology, punctuality, current issue, approachable, language use, and communication help in differentiating lecturers" teaching performance and students" perceptions of teaching quality. The findings of this study suggest that the lecturers should consider these dimensions during lecturer-student interaction in the classroom.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Students as the major consumers of the higher education system are in a position to evaluate teaching because they are the observers of the lecturers in the classroom (Su, 1995). Hussin et al (2008) suggested that student's perceptions are important in assessing and evaluating the quality of teaching as they form the end part of the process whereby a high quality teaching is expected to transform into a better performance in students. Feedback from students may help lecturers to improve their teaching performances.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the student evaluation is seen as a key step in the drive to improve the effectiveness of teaching and learning and raise educational standards (Santiago & Benavides, 2009). Hussin, Jusoff, and Wan-Omar (2008) posited that students' perceptions are important in assessing and evaluating the quality of teaching. Gold (2001) regards SET as a useful tool to improve classroom instruction, student learning, and to foster professional growth of the teacher, and also the results of such evaluation are used for administrative/personnel decisions.…”
Section: Student Evaluation Of Teachingmentioning
confidence: 99%